Methods to enhance the thermal properties of organic phase change materials: A review. (2022) - Duttaluru, Gowthami; Singh, Pooja; Kumar Ansu, Alok; kumar Sharma, Ravi; kumar, Amit; Mishra, Shivam
Abstract: The rate of energy consumption has been increasing in the recent years with the expanding population. Renewable energy sources have been centre of attention for many researchers around the globe, since they are available abundantly. Solar thermal energy storage systems accumulates energy from the solar field, using a phase change material. Organic phase change materials have desirable physical, chemical and thermal properties necessary for thermal energy storage system applications. Energy storage capacity of the organic phase change materials is often limited due to their low thermal conductivity and leakage during phase transition. Therefore, various methods have been developed to enhance the thermal conductivity of PCMs. Developing hydrophobic PCMs, intercalation composite PCMs, inserting nano fibres in PCMs and introducing carbon additives like CNT, MWCNT and EG in PCMs addressed the challenges mentioned above. Thermal characterization of the PCMs after introducing these materials showed a significant increase in thermal conductivity. The current work deals with the various methods adopted by researchers to enhance the thermal conductivity of the organic phase change materials.